A composite hydrophobic fiber membrane based on a friction nanogenerator and a preparation method thereof
Patent Information
- Application Number
- CN202510759461.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-09
AI Technical Summary
[0005]为此,本发明所要解决的技术问题在于提供一种基于摩擦纳米发电机的复合型疏水纤维膜及其制备方法,以解决现有改性聚偏二氟乙烯纤维膜在用于高湿环境下摩擦纳米发电机的摩擦层时,其输出电性能不高等技术问题
[0028]1、本发明基于摩擦纳米发电机的复合型疏水纤维膜的制备方法,通过静电纺丝和静电喷雾相结合的工艺,将具有特定含量100~200nm的方硼石微粒的较高分子量的高浓度PVDF静电纺丝液与具有特定含量80~150nm的疏水纳米颗粒(二氧化钛或二氧化锆)的较低分子量的低浓度PVDF静电喷雾液采用特定的比例同步进行静电纺丝和静电喷雾,使得在静电纺丝过程中,100~200nm的方硼石微粒包埋到高浓度较高分子量的PVDF静电纺丝液形成的纤维丝中,同时使得低浓度PVDF静电喷雾液中较低分子量的PVDF形成微米级PDVF微球附着在高浓度较高分子量的PVDF经静电纺丝液形成的纤维丝上,并且一部分疏水纳米颗粒(二氧化钛或二氧化锆)附着在微米级PDVF微球上,另一部分疏水纳米颗粒(二氧化钛或二氧化锆)附着在高浓度较高分子量的PVDF经静电纺丝液形成的纤维丝上,从而形成具有良好疏水性的复合型疏水纤维膜,将该复合型疏水纤维膜用于摩擦纳米发电机的摩擦层,能够使其在高湿环境下保持良好的稳定性以及较高的输出电性能。
Smart Images

Figure CN120625262B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of triboelectric power generation materials technology. Specifically, it relates to a composite hydrophobic fiber membrane based on a triboelectric nanogenerator and its preparation method. Background Technology
[0002] Triboelectric nanogenerators (TENGs) utilize the principles of triboelectric charging and electrostatic induction to generate current through contact charging and electrostatic induction. This can, to some extent, solve the problem of powering devices with traditional power sources. Therefore, in recent years, TENGs have shown great promise in wearable devices, the Internet of Things (IoT), medical monitoring, and ocean energy harvesting. The working principle of TENGs is based on contact charging and electrostatic induction effects. The triboelectric layer structure is the core of the entire TENG, so the dielectric material attached to the triboelectric layer plays a crucial role, as it directly affects the TENG's performance, including charge generation, storage, and transfer. Common dielectric materials include polyamide, aluminum, brass, polyurethane, and polytetrafluoroethylene (PTFE).
[0003] Polyvinylidene fluoride (PVDF) possesses high dielectric constant, high chemical stability, ease of processing and molding, and good environmental adaptability compared to other dielectric materials, and has been widely studied as a substrate for transducers (TENGs). PVDF has four crystalline phases (α, β, σ, and γ), with the α phase being the most common and the β phase exhibiting the highest electrical properties. The β phase crystal form is typically formed under specific processing conditions, such as low-temperature solution crystallization, mechanical stretching, and high-voltage electric field polarization. A relatively economical and convenient method is to stretch the polymer chains through electrospinning technology, causing the α phase to transform into the β phase. However, the β phase content obtained by optimizing solvents and spinning parameters alone is insufficient to meet practical application requirements. Therefore, to obtain more β phase during electrospinning, the introduction of nanofillers provides a new approach to improving the electrical properties of PVDF-based TENGs. Nanofillers such as graphene, nano-Ag, BaTiO3 nanoparticles, and other nanofillers, by uniformly dispersing them in a PVDF solution and then preparing thin films using electrospinning technology, effectively increase the β phase content. However, the addition of nanofillers increases the concentration of the PVDF spinning solution. Excessive addition of nanofillers can lead to agglomeration, increasing fiber diameter and reducing β-phase crystallization. Therefore, it is necessary to find a new type of nanofiller that can achieve a high β-phase content with a small addition.
[0004] Existing technologies use tourmaline and silica as fillers for polyvinylidene fluoride (PVDF) and employ electrospinning to prepare the triboelectric layer for triboelectric nanogenerators. This allows for the production of films with high β-phase content without filler agglomeration, and these films exhibit high electrical output performance and excellent mechanical properties under high humidity conditions. However, tourmaline's high surface polarity leads to functional decay and charge instability, and humidity or water contact may weaken its electrode effect. Furthermore, tourmaline's strong hydrophilicity necessitates the use of surface modifiers to reduce its surface energy. On the other hand, silica particles, due to their high specific surface area and the polarity of their surface hydroxyl groups (-OH), are prone to agglomeration within the PVDF matrix due to van der Waals forces or electrostatic interactions, resulting in uneven fiber morphology or localized breakage. Therefore, further improvements are necessary to enhance the electrical output performance of PVDF fiber films while maintaining good stability under high humidity conditions. Summary of the Invention
[0005] Therefore, the technical problem to be solved by the present invention is to provide a composite hydrophobic fiber membrane based on triboelectric nanogenerator and its preparation method, so as to solve the technical problem that the output electrical performance of the existing modified polyvinylidene fluoride fiber membrane is not high when used as the triboelectric layer of triboelectric nanogenerator in high humidity environment.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0007] A composite hydrophobic fiber membrane based on a triboelectric nanogenerator is composed of a polyvinylidene fluoride (PVDF) nanofiber membrane, borosilicate microparticles, hydrophobic nanoparticles, and PVDF microspheres. The borosilicate microparticles are embedded in the filaments of the PVDF nanofiber membrane, and the PVDF microspheres are attached to the filaments of the PVDF nanofiber membrane. Some of the hydrophobic nanoparticles are uniformly attached to the PVDF microspheres, and the other part of the hydrophobic nanoparticles are uniformly attached to the filaments of the PVDF nanofiber membrane. The hydrophobic nanoparticles are titanium dioxide nanoparticles or zirconium dioxide nanoparticles.
[0008] The aforementioned composite hydrophobic fiber membrane based on triboelectric nanogenerators has a polyvinylidene fluoride (PVDF) nanofiber membrane thickness of 80–120 μm and a fiber diameter of 160–170 nm (the fiber diameter directly affects the specific surface area and porosity of the composite hydrophobic fiber membrane; this invention controls the fiber diameter within the range of 160–170 nm. Such uniform and fine fibers can form a highly porous mesh structure, increasing both the specific surface area and surface roughness of the composite membrane, thereby effectively enhancing its charge trapping ability); the borosilicate microparticles have a particle size of 1… The diameter of the hydrophobic nanoparticles is 80–150 nm, and the diameter of the polyvinylidene fluoride (PVDF) microspheres is 0.5–5 μm. By controlling the diameters of the borosilicate microparticles, hydrophobic nanoparticles, and PVDF microspheres above a PVDF nanofiber membrane of a specific thickness within the above ranges, adhesion between PVDF nanofibers can be effectively avoided, ensuring that the PVDF nanofibers maintain a uniform filamentous structure. Furthermore, the PVDF microspheres can effectively support the PVDF nanofibers to form a stable framework structure, which is beneficial for charge transfer between PVDF nanofibers. The hydrophobic nanoparticles are moved to improve the electrical properties of the composite hydrophobic fiber membrane; the mass of the borosilicate microparticles is 0.5-3.0 wt% (preferably 1.0-2.5 wt%) of the polyvinylidene fluoride fiber membrane, the mass of the hydrophobic nanoparticles is 0.2-1.0 wt% of the polyvinylidene fluoride microspheres, and the polyvinylidene fluoride microspheres are 10-20 wt% of the polyvinylidene fluoride fiber membrane; the mass ratio of the hydrophobic nanoparticles attached to the polyvinylidene fluoride microspheres to the hydrophobic nanoparticles attached to the fibers of the polyvinylidene fluoride nanofiber membrane is (10-20):1; when the hydrophobic nanoparticles attached to the polyvinylidene fluoride microspheres are... When the proportion of hydrophobic nanoparticles is within the above range, it ensures that the polyvinylidene fluoride microspheres and hydrophobic nanoparticles form a secondary structure with hydrophobic properties on the surface of the composite hydrophobic fiber membrane, enabling the composite hydrophobic fiber membrane to maintain excellent power generation performance in high humidity environments. The remaining hydrophobic nanoparticles are attached to the fiber filaments, which can endow the fiber membrane surface with a certain self-cleaning function (the photocatalytic effect of titanium dioxide or zirconium dioxide can degrade pollutants such as proteins and oxides adsorbed on the surface of the composite fiber membrane in humid environments), thereby helping to further improve the stability of the power generation performance of the composite hydrophobic fiber membrane in high humidity environments.
[0009] A method for preparing a composite hydrophobic fiber membrane based on a triboelectric nanogenerator includes the following steps:
[0010] Step (1): Disperse the borate powder in N,N-dimethylformamide by ultrasonication to obtain a borate dispersion; add the first polyvinylidene fluoride powder to the borate dispersion, heat and stir until the first polyvinylidene fluoride is completely dissolved to obtain an electrospinning solution.
[0011] Step (2): Disperse the hydrophobic nanoparticles ultrasonically into N,N-dimethylformamide to obtain a hydrophobic nanoparticle dispersion. The hydrophobic nanoparticles are titanium dioxide nanoparticles or zirconium dioxide nanoparticles. Add the second polyvinylidene fluoride powder to the hydrophobic nanoparticle dispersion and heat and stir until the second polyvinylidene fluoride is completely dissolved to obtain an electrostatic spray liquid.
[0012] Step (3): Place the electrospinning solution and the electrospray solution in the electrospinning equipment to perform electrospinning and electrospraying simultaneously, and collect the electrospinning jet products;
[0013] Step (4): The electrostatic jet products collected on the collector are dried. After the drying process is completed, the above-mentioned composite hydrophobic fiber membrane based on triboelectric nanogenerator is obtained.
[0014] In the above-mentioned method for preparing a composite hydrophobic fiber membrane based on a triboelectric nanogenerator, in step (1), the particle size of the borate powder is 100-200 nm, and the mass of the borate powder in the electrospinning solution is 0.5-3.0 wt% of the mass of the first polyvinylidene fluoride. The ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 30-60 kHz for 1.5-3 h at room temperature. If the particle size of the borate powder used is too large, the electric field force will be insufficient to pull the fiber filaments during electrospinning, and some borate powder will precipitate at the bottom of the container due to its large particle size, resulting in uneven distribution of borate particles in the formed fiber filaments. If the mass ratio of borate powder to the first polyvinylidene fluoride in the electrospinning solution is too large, the electrospinning solution will be subjected to uneven electric field force during electrospinning, resulting in fiber filaments of different shapes, or the fiber filaments will easily stick together. If the amount of borate powder in the electrospinning solution is too small, the improvement effect of borate on the first polyvinylidene fluoride fiber membrane will be insignificant.
[0015] In the above-mentioned method for preparing a composite hydrophobic fiber membrane based on a triboelectric nanogenerator, in step (1), the average relative molecular mass of the first polyvinylidene fluoride powder is 500,000 to 600,000, the mass fraction of the first polyvinylidene fluoride in the electrospinning solution is 15 to 20 wt%, and the heating and stirring conditions are: stirring at a temperature of 65 to 80°C and a stirring speed of 350 to 500 rpm for 2 to 5 hours; by using the first polyvinylidene fluoride powder with the above molecular weight and controlling its mass fraction within 15 to 20 wt%, the viscosity of the obtained electrospinning solution is moderate, which is conducive to the formation of uniform and stable nanofibers by electrospinning. This invention controls the particle size and amount of borate powder in the electrospinning solution, as well as the relative molecular mass and mass fraction of the first polyvinylidene fluoride powder. This allows the first polyvinylidene fluoride to dissolve in N,N-dimethylformamide to form an electrospinning solution with suitable viscosity. Furthermore, the borate powder can be uniformly and stably distributed in the electrospinning solution. This not only facilitates the spinning of polyvinylidene fluoride nanofibers with uniform thickness, but also ensures that the borate powder is uniformly coated on the polyvinylidene fluoride nanofibers during the electrospinning process. This, in turn, helps the nanofibers effectively improve the electrical properties of the composite fiber membrane during triboelectric power generation.
[0016] In the above-mentioned method for preparing a composite hydrophobic fiber membrane based on a triboelectric nanogenerator, in step (2), the particle size of the hydrophobic nanoparticles is 80-150 nm, and the mass of the hydrophobic nanoparticles in the electrostatic spray liquid is 0.2-1.0 wt% of the mass of the second polyvinylidene fluoride. If the particle size of the hydrophobic nanoparticles is greater than 150 nm or the amount of hydrophobic nanoparticles in the electrostatic spray liquid is too large, it will be difficult for the hydrophobic nanoparticles to adhere to the polyvinylidene fluoride microspheres formed by electrostatic spraying, or in other words, too many hydrophobic nanoparticles will adhere to the polyvinylidene fluoride nanofibers, thereby causing adhesion between the polyvinylidene fluoride nanofibers. If the particle size of the hydrophobic nanoparticles is less than 80 nm or the amount of hydrophobic nanoparticles in the electrostatic spray liquid is too small, it will be difficult for them to form an effective hydrophobic structure on the polyvinylidene fluoride nanofiber membrane. The ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 40-60 kHz for 60-90 min at room temperature.
[0017] In the above-mentioned method for preparing the composite hydrophobic fiber membrane based on triboelectric nanogenerator, in step (2), the average relative molecular mass of the second polyvinylidene fluoride powder is 400,000 to 450,000, the mass fraction of the second polyvinylidene fluoride in the electrostatic spray liquid is 4 to 10 wt%, and the heating and stirring conditions are: stirring at 350 to 500 rpm for 2 to 3 hours at a temperature of 65 to 80°C. This invention, by controlling the particle size and amount of hydrophobic nanoparticles in the electrostatic spray liquid, and the average relative molecular mass and mass fraction of the second polyvinylidene fluoride powder used, enables the spraying of polyvinylidene fluoride microspheres (with diameters concentrated in the range of 2 to 4 μm) under the electric field conditions of this invention, and ensures that most of the hydrophobic nanoparticles can adhere to the polyvinylidene fluoride microspheres.
[0018] In the above-mentioned method for preparing composite hydrophobic fiber membranes based on triboelectric nanogenerators, in step (3), the electrospinning equipment is an electrospinning machine capable of electrospinning and electrospraying; when electrospinning and electrospraying are performed simultaneously: the voltage of the high-voltage electrostatic field is 18-20kV (if the voltage of the high-voltage electrostatic field is too high, it will cause the fiber filaments to be uneven due to the excessive electric field force; if the voltage of the high-voltage electrostatic field is too low, it will cause the fiber filaments to be uneven due to the insufficient electric field force to pull the fiber filaments); the propulsion rates of the electrospinning liquid and the electrospraying liquid are the same, both being 1.0-1.2mL·h. -1 The distance between the injection nozzle tip and the aluminum foil collector should be 15–18 cm (too short a distance will result in incomplete evaporation of the solvent in the electrospinning solution and electrostatic spray, leading to fiber adhesion; too long a distance will result in incomplete fiber collection). The temperature should be controlled within the range of 30–45℃, and the relative humidity within the range of 40–50% (too low a temperature or too high a humidity will result in incomplete solvent evaporation and fiber adhesion; too high a temperature or too low a humidity will result in brittle fibers, affecting their mechanical properties). By controlling the electrospinning solution and electrostatic spray solution… The dosage ratio should be such that the mass of polyvinylidene fluoride microspheres in the final composite hydrophobic fiber membrane is 10-20 wt% of the mass of the polyvinylidene fluoride fiber membrane. If the amount of electrospinning solution is too large, the hydrophobic structure formed by the hydrophobic nanoparticles and polyvinylidene fluoride microspheres will be relatively small, affecting the hydrophobic properties of the composite hydrophobic fiber membrane. If the amount of electrospinning solution is too large, the polyvinylidene fluoride microspheres will be too densely distributed on the polyvinylidene fluoride nanofibers, causing the polyvinylidene fluoride nanofibers to stick together, thereby reducing the electrical properties of the prepared composite hydrophobic fiber membrane.
[0019] This invention, by controlling the ratio of electrospinning solution (containing a specific amount of 100-200 nm borosilicate powder and a first polyvinylidene fluoride with an average relative molecular mass of 600,000) and electrospray solution (containing a specific amount of 80-150 nm hydrophobic nanoparticles and a second polyvinylidene fluoride with an average relative molecular mass of 400,000), the voltage of the high-voltage electrostatic field, the propulsion rate of the electrospinning solution and the electrospray solution, the distance between the tip of the injection nozzle and the aluminum foil collector, and the working temperature and humidity during the electrospinning and electrospraying processes, enables electrospraying to form polyvinylidene fluoride microspheres of uniform size, and electrospinning to form nanofibers of uniform thickness and small diameter. Furthermore, the polyvinylidene fluoride microspheres formed by spraying can be uniformly attached to the polyvinylidene fluoride nanofibers formed by electrospinning, while the specific proportion of hydrophobic nanoparticles in the electrospray solution... The particles adhere to the polyvinylidene fluoride (PVDF) microspheres, while the remaining particles adhere to the PVDF nanofibers formed by electrospinning, endowing the composite hydrophobic fiber membrane with excellent hydrophobic properties. Under the process conditions of this invention, the borate particles in the electrospinning solution can be uniformly embedded in the PVDF nanofiber membrane fibers (some larger diameter borate particles will protrude from the fibers), which is beneficial for them to fully play their role in improving the power generation performance of the composite fiber membrane during triboelectric power generation. At the same time, the PVDF microspheres, as a skeleton, support the uniform and relatively fine PVDF nanofibers to form a network structure with high porosity, which increases the specific surface area of the composite hydrophobic fiber membrane and also increases its surface roughness, which is beneficial for improving the charge trapping ability of the membrane, thereby further improving the power generation performance of the composite hydrophobic fiber membrane.
[0020] In the above-mentioned method for preparing the composite hydrophobic fiber membrane based on triboelectric nanogenerator, the drying conditions in step (4) are: 50-60℃, drying for 12-16h. Excessive drying time or excessively high drying temperature will lead to a decrease in the brittle and hard mechanical properties of the composite hydrophobic fiber membrane. Insufficient drying time or excessively low drying temperature may cause residual solvent to adhere to the surface of the fiber membrane, affecting its electrical properties. The thickness of the composite hydrophobic fiber membrane obtained after drying is 80-120μm. If the composite hydrophobic fiber membrane is less than 80μm, its mechanical strength will be insufficient to meet practical application requirements. If its thickness is greater than 120μm, the difficulty of charge transfer will increase, affecting its electrical properties. This invention, by controlling the drying temperature, drying time, and thickness of the composite hydrophobic fiber membrane, can ensure that the prepared composite hydrophobic fiber membrane has good electrical properties while meeting the mechanical strength requirements for use.
[0021] In the above-mentioned method for preparing a composite hydrophobic fiber membrane based on a triboelectric nanogenerator, in step (1), the particle size of the borosilicate powder is 100-200 nm, the mass of the borosilicate powder in the electrospinning solution is 1.5 wt% of the mass of the first polyvinylidene fluoride, and the ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 40 kHz for 2 h at room temperature.
[0022] The average relative molecular mass of the first polyvinylidene fluoride powder is 600,000, the mass fraction of the first polyvinylidene fluoride in the electrospinning solution is 20 wt%, and the heating and stirring conditions are: stirring at 70°C and 400 rpm for 4 hours.
[0023] In step (2), the particle size of the hydrophobic nanoparticles is 80-150 nm, the mass of the hydrophobic nanoparticles in the electrostatic spray liquid is 0.6 wt% of the mass of the second polyvinylidene fluoride, and the ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 40 kHz for 60 min at room temperature.
[0024] The average relative molecular mass of the second polyvinylidene fluoride powder is 400,000, the mass fraction of the second polyvinylidene fluoride in the electrostatic spray liquid is 8 wt%, and the heating and stirring conditions are: stirring at 70℃ and stirring at 400 rpm for 2 hours.
[0025] In step (3), the electrospinning equipment is an electrospinning machine capable of electrospinning and electrospraying; when electrospinning and electrospraying are performed simultaneously: the volume ratio of the electrospinning solution to the electrospraying solution is 2:1, the voltage of the high-voltage electrostatic field is 20kV, and the propulsion rates of the electrospinning solution and the electrospraying solution are the same, both being 1.2mL·h. -1 The distance between the tip of the injection nozzle and the aluminum foil collector is 18cm, the temperature is 40℃, and the relative humidity is 40%.
[0026] In step (4), the drying conditions are: 55℃, drying for 12h; the thickness of the composite hydrophobic fiber membrane obtained by drying is 80~90μm.
[0027] The technical solution of the present invention achieves the following beneficial technical effects:
[0028] 1. This invention relates to a method for preparing a composite hydrophobic fiber membrane based on a triboelectric nanogenerator. The method combines electrospinning and electrospraying processes. A high-concentration PVDF electrospinning solution with a specific molecular weight of 100-200 nm borate microparticles and a low-concentration PVDF electrospray solution with a specific molecular weight of 80-150 nm hydrophobic nanoparticles (titanium dioxide or zirconium dioxide) are simultaneously electrospinned and electrosprayed in a specific ratio. This allows the 100-200 nm borate microparticles to be embedded within the fibers formed by the high-concentration, high-molecular-weight PVDF electrospinning solution during electrospinning, while simultaneously reducing the concentration of the low-concentration PVDF. In a high-concentration PVDF electrospinning solution, lower molecular weight PVDF forms micron-sized PDVF microspheres that attach to fibers formed from high-concentration, higher molecular weight PVDF through electrospinning. Additionally, some hydrophobic nanoparticles (titanium dioxide or zirconium dioxide) are attached to the micron-sized PDVF microspheres, while another portion are attached to the fibers formed from high-concentration, higher molecular weight PVDF through electrospinning. This results in a composite hydrophobic fiber membrane with excellent hydrophobicity. Using this composite hydrophobic fiber membrane as the friction layer in a triboelectric nanogenerator enables it to maintain good stability and high output electrical performance under high humidity conditions.
[0029] 2. Compared with tourmaline used in the background technology, borate is free of toxic elements and more environmentally friendly. Borate has stronger polarity than tourmaline, and using it as a filler for polyvinylidene fluoride (PVDF) can significantly improve the conductivity of the electrospinning solution. This results in more uniform morphology of PVDF fibers obtained through electrospinning, allowing the electrospinning solution to respond to a stronger electric field, producing finer fibers. Furthermore, it facilitates the recrystallization of PVDF under a high-voltage electric field, yielding PVDF fibers with more β-phase, thereby improving the composite hydrophobic fiber membrane. Electrical properties: This invention uses borosilicate as the filler for the first polyvinylidene fluoride (PVDF) and titanium dioxide or zirconium dioxide as hydrophobic nanoparticles. These nanoparticles and PVDF microspheres are electrostatically sprayed together to form a hydrophobic structure. The PVDF microspheres can adsorb electrons, thereby supporting the PVDF nanofibers to form a high-porosity mesh framework structure (the finer the fiber, the better the porosity). The high porosity is beneficial for adsorbing more electrons during triboelectric power generation, thereby further improving the electrical properties of the composite hydrophobic fiber membrane. This invention, by controlling the diameter of the polyvinylidene fluoride nanofiber membrane, the diameter of the borate microparticles, the diameter of the hydrophobic nanoparticles, the diameter of the polyvinylidene fluoride microspheres, the amount of borate microparticles, hydrophobic nanoparticles, and polyvinylidene fluoride microspheres in the composite hydrophobic fiber membrane, and the distribution of the hydrophobic nanoparticles, enables the composite hydrophobic fiber membrane to have better hydrophobic properties. Furthermore, it enables the borate microparticles and hydrophobic nanoparticles to work synergistically to improve the electrical properties of the composite hydrophobic fiber membrane and the stability of its electrical properties in high humidity environments. Attached Figure Description
[0030] Figure 1a SEM images of PVDF nanofiber membranes in embodiments of the present invention;
[0031] Figure 1b SEM image of the PVDF / B composite nanofiber membrane in this embodiment of the invention (boronite doping content is 1.5 wt%);
[0032] Figure 1c SEM image of the PVDF / BT composite hydrophobic fiber membrane in this embodiment of the invention (boronite doping amount is 1.5wt%; titanium dioxide doping amount is 0.6wt%).
[0033] Figure 1d SEM image of the PVDF / BZ composite hydrophobic fiber membrane in this embodiment of the invention (boronite doping amount is 1.5wt%; zirconium dioxide doping amount is 0.6wt%).
[0034] Figure 2a EDS surface scan of PVDF nanofiber membrane in the embodiments of the present invention;
[0035] Figure 2b EDS surface scan of PVDF / B composite nanofiber membrane in this embodiment of the invention (boronite doping amount is 1.5wt%);
[0036] Figure 3a EDS surface scan of the PVDF / BT composite hydrophobic fiber membrane in this embodiment of the invention (boronite doping amount is 1.5wt%; titanium dioxide doping amount is 0.6wt%).
[0037] Figure 3b EDS surface scan of the PVDF / BZ composite hydrophobic fiber membrane in this embodiment of the invention (boronite doping amount is 1.5wt%; zirconium dioxide doping amount is 0.6wt%).
[0038] Figure 4 XRD patterns of PVDF nanofiber membranes, PVDF / B composite nanofiber membranes (1.5 wt% borate doping), PVDF / BT composite hydrophobic fiber membranes (1.5 wt% borate doping; 0.6 wt% titanium dioxide doping), and PVDF / BZ composite hydrophobic fiber membranes (1.5 wt% borate doping; 0.6 wt% zirconium dioxide doping) prepared in the embodiments of the present invention;
[0039] Figure 5 FTIR spectra of PVDF nanofiber membranes, PVDF / B composite nanofiber membranes (1.5 wt% borate doping), PVDF / BT composite hydrophobic fiber membranes (1.5 wt% borate doping; 0.6 wt% titanium dioxide doping), and PVDF / BZ (1.5 wt% borate doping; 0.6 wt% zirconium dioxide doping) prepared in the embodiments of the present invention;
[0040] Figure 6a Diagram of the diameter distribution of microspheres in the PVDF / BT composite hydrophobic fiber membrane (1.5 wt% borosilicate doping and 0.6 wt% titanium dioxide doping) prepared in this embodiment of the invention;
[0041] Figure 6b Diagram of micro / nanosphere diameter distribution in the PVDF / BZ composite hydrophobic fiber membrane (1.5 wt% borosilicate doping; 0.6 wt% zirconium dioxide doping) prepared in this embodiment of the invention;
[0042] Figure 7a , Figure 7b and Figure 7cWhen the PVDF / B composite nanofiber membranes (with borosilicate doping amounts of 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, and 2.5wt%) prepared in the embodiments of the present invention are used as the friction layer of TENG, the short-circuit current, transferred charge, and open-circuit voltage of TENG are measured.
[0043] Figure 8a , Figure 8b and Figure 8c When the PVDF / BT composite hydrophobic fiber membranes (with borosilicate doping of 1.5 wt% and titanium dioxide doping of 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt%, and 1.0 wt%) prepared in the embodiments of the present invention are used as the friction layer of TENG, the short-circuit current, transferred charge, and open-circuit voltage of TENG are measured.
[0044] Figure 9a , Figure 9b and Figure 9c When the PVDF / BZ composite hydrophobic fiber membranes (with borosilicate doping of 1.5 wt% and zirconium doping of 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt%, and 1.0 wt%) prepared in the embodiments of the present invention are used as the friction layer of TENG, the short-circuit current, transferred charge, and open-circuit voltage of TENG are measured.
[0045] Figure 10 The dielectric constant test results of the PVDF / B composite nanofiber membrane, PVDF / B composite nanofiber membrane (1.5 wt% borate doping), PVDF / BT composite hydrophobic fiber membrane (1.5 wt% borate doping; 0.6 wt% titanium dioxide doping), and PVDF / BZ (1.5 wt% borate doping; 0.6 wt% zirconium dioxide doping) prepared in the embodiments of the present invention are shown in the figure.
[0046] Figure 11 The permeability test results of the PVDF / B composite nanofiber membrane (1.5 wt% borate doping), PVDF / BT composite hydrophobic fiber membrane (1.5 wt% borate doping; 0.6 wt% titanium dioxide doping), and PVDF / BZ (1.5 wt% borate doping; 0.6 wt% zirconium dioxide doping) prepared in the embodiments of the present invention are shown in the figure.
[0047] Figure 12The dielectric loss test results of the PVDF / B composite nanofiber membrane (1.5 wt% borate doping), PVDF / BT composite hydrophobic fiber membrane (1.5 wt% borate doping; 0.6 wt% titanium dioxide doping), and PVDF / BZ (1.5 wt% borate doping; 0.6 wt% zirconium dioxide doping) prepared in the embodiments of the present invention are shown in the figure.
[0048] Figure 13 The graph shows the charge transfer test results of the PVDF / B composite nanofiber membrane (1.5 wt% borate doping), PVDF / BT composite hydrophobic fiber membrane (1.5 wt% borate doping; 0.6 wt% titanium dioxide doping), and PVDF / BZ (1.5 wt% borate doping; 0.6 wt% zirconium dioxide doping) prepared in the embodiments of the present invention under different humidity conditions.
[0049] Figure 14a , Figure 14b , Figure 14c and Figure 14d The images show the surface of four types of fiber membranes prepared according to embodiments of the present invention: PVDF nanofiber membrane, PVDF / B composite nanofiber membrane (1.5 wt% borate doping), PVDF / BT composite hydrophobic fiber membrane (1.5 wt% borate doping; 0.6 wt% titanium dioxide doping), and PVDF / BZ (1.5 wt% borate doping; 0.6 wt% zirconium dioxide doping). These images were obtained under a 200x optical microscope.
[0050] Figure 15a , Figure 15b , Figure 15c and Figure 15d The figures show the water contact angle test results of four types of fiber membranes prepared in the embodiments of the present invention: PVDF nanofiber membrane, PVDF / B composite nanofiber membrane (1.5 wt% borate doping), PVDF / BT composite hydrophobic fiber membrane (1.5 wt% borate doping; 0.6 wt% titanium dioxide doping), and PVDF / BZ (1.5 wt% borate doping; 0.6 wt% zirconium dioxide doping).
[0051] Figure 16 A schematic diagram of the microstructure of a PVDF / / BT composite hydrophobic fiber membrane (1.5 wt% borosilicate doping and 0.6 wt% titanium dioxide doping);
[0052] Figure 17a TENG current and output power under different loads based on PVDF / BT composite hydrophobic fiber membrane (boronite doping of 1.5wt%; titanium dioxide doping of 0.6wt%);
[0053] Figure 17b TENG current and output power under different loads based on PVDF / BZ composite hydrophobic fiber membrane (boronite doping of 1.5wt%; zirconium dioxide doping of 0.6wt%);
[0054] Figure 18a The short-circuit current of TENG based on PVDF / BT composite hydrophobic fiber membrane (1.5wt% borosilicate doping and 0.6wt% titanium dioxide doping) at 14.4k cycle period;
[0055] Figure 18b The short-circuit current of TENG based on PVDF / BZ composite hydrophobic fiber membrane (1.5wt% borosilicate doping and 0.6wt% zirconium dioxide doping) at 14.4k cycle time;
[0056] Figure 19a Charging curve of TENG capacitor based on PVDF / BT composite hydrophobic fiber membrane (boronite doping amount of 1.5wt%; titanium dioxide doping amount of 0.6wt%);
[0057] Figure 19b Charging curves of a TENG capacitor based on a PVDF / BZ composite hydrophobic fiber membrane (1.5 wt% borosilicate doping and 0.6 wt% zirconium dioxide doping);
[0058] Figure 20a TENG charging test circuit diagram based on PVDF / BT composite hydrophobic fiber membrane (boronite doping amount of 1.5wt%; titanium dioxide doping amount of 0.6wt%);
[0059] Figure 20b Circuit diagram of TENG power supply system based on PVDF / BT composite hydrophobic fiber membrane (boronite doping amount of 1.5wt%; titanium dioxide doping amount of 0.6wt%). Detailed Implementation
[0060] 1. Preparation of composite hydrophobic fiber membranes
[0061] (1) Preparation of electrospinning solution
[0062] A. Add 20g of polyvinylidene fluoride powder (PVDF, with an average relative molecular mass of 600,000) to N,N-dimethylformamide. Stir at 400rpm for 4 hours at 70℃ until the polyvinylidene fluoride is completely dissolved to obtain electrospinning solution A. The mass fraction of polyvinylidene fluoride in electrospinning solution A is 20wt%.
[0063] B. Add borate powder (particle size 100-200 nm) to 100 mL of N,N-dimethylformamide and ultrasonically disperse at 40 kHz for 2 h at room temperature to obtain borate dispersion; add first polyvinylidene fluoride powder (PVDF, average relative molecular mass 600,000) to borate dispersion and stir at 400 rpm for 4 h at 70 °C until the first polyvinylidene fluoride is completely dissolved to obtain electrospinning solution B; in electrospinning solution B, the mass fraction of PVDF is 20 wt% and the mass of borate powder is 1.5 wt% of the mass of PVDF.
[0064] (2) Preparation of electrostatic spray liquid
[0065] A. Titanium dioxide powder (particle size 80-150 nm) was added to 100 mL of N,N-dimethylformamide and ultrasonically dispersed at 40 kHz for 60 min at room temperature to obtain a titanium dioxide dispersion. Second polyvinylidene fluoride powder (PVDF, average relative molecular mass 400,000) was added to the titanium dioxide dispersion, and the mixture was stirred at 400 rpm for 2 h at 70 °C until the second PVDF was completely dissolved to obtain electrostatic spray liquid A. The mass fraction of titanium dioxide powder in electrostatic spray liquid A was 0.6 wt%, and the mass fraction of the second PVDF was 8 wt%.
[0066] B. Zirconia powder (particle size 80-150 nm) was added to 100 mL of N,N-dimethylformamide and ultrasonically dispersed at 40 kHz for 60 min at room temperature to obtain a titanium dioxide dispersion. Second polyvinylidene fluoride powder (PVDF, average relative molecular mass 400,000) was added to the titanium dioxide dispersion, and the mixture was stirred at 400 rpm for 2 h at 70 °C until the second PVDF was completely dissolved to obtain electrostatic spray liquid B. The mass fraction of zirconium dioxide powder in electrostatic spray liquid B was 0.6 wt%, and the mass fraction of the second PVDF was 8 wt%.
[0067] (3) Preparation of PVDF nanofiber membranes
[0068] Electrospinning solution A was placed in the syringe of the electrospinning equipment (Qingdao Pansi Technology PS-ZJ-01 electrospinning machine) for electrospinning. Under a high voltage of 20kV, the injection pump was used at a rate of 1.2mL / h. -1 The device was continuously propelled at a constant speed; the distance between the syringe nozzle tip and the aluminum foil collector was fixed at 18 cm; the temperature was maintained at 40℃ and the relative humidity at around 40%; after continuous collection for about 5 hours, it was dried in an oven at 55℃ for 12 hours to obtain a PVDF nanofiber membrane with a thickness of about 80 μm.
[0069] (4) Preparation of PVDF / B composite nanofiber membranes
[0070] Electrospinning solution B was placed in the syringe of the electrospinning equipment (Beijing Yongkang Leyue SS-X3 electrospinning machine) for electrospinning. Under a high voltage of 20kV, the injection pump was used at a rate of 1.2mL / h. -1 The device was continuously propelled at a constant speed; the distance between the syringe nozzle tip and the aluminum foil collector was fixed at 18 cm; the temperature was maintained at 40℃ and the relative humidity at around 40%; after continuous collection for about 5 hours, it was dried in an oven at 55℃ for 12 hours to obtain a PVDF / B composite nanofiber membrane with a thickness of about 80 μm.
[0071] (5) Preparation of PVDF / BT composite hydrophobic fiber membrane
[0072] Electrospinning solution B and electrospray solution A were placed in the syringes of the electrospinning equipment (Beijing Yongkang Leyue SS-X3 electrospinning machine) for simultaneous electrospinning and electrospraying. Electrospray solution A was filled to the middle position of three 10mL syringes, while the syringes on both sides were filled with electrospinning solution B. Under a high voltage of 20kV, the injection pump was used at a rate of 1.2mL·h. -1 The device is continuously advanced at a constant speed; the distance between the syringe nozzle tip and the aluminum foil collector is fixed at 18cm; the temperature is maintained at 40℃ and the relative humidity is around 40%; after continuous collection for about 5 hours, it is dried in an oven at 55℃ for 12 hours to obtain a PVDF / BT composite hydrophobic fiber membrane with a thickness of about 80μm.
[0073] (6) Preparation of PVDF / BZ composite hydrophobic fiber membrane
[0074] Electrospinning solution B and electrospray solution B were placed in the syringes of the electrospinning equipment (Beijing Yongkang Leyue SS-X3 electrospinning machine) for simultaneous electrospinning and electrospraying. Electrospray solution B was filled to the middle position of three 10mL syringes, while the syringes on both sides were filled with electrospinning solution B. Under a high voltage of 20kV, the injection pump was used at a rate of 1.2mL·h. -1 The device is continuously advanced at a constant speed; the distance between the syringe nozzle tip and the aluminum foil collector is fixed at 18 cm; the temperature is maintained at 40℃ and the relative humidity is around 40%; after continuous collection for about 5 hours, it is dried in an oven at 55℃ for 12 hours to obtain a PVDF / BZ composite hydrophobic fiber membrane with a thickness of about 80 μm.
[0075] Using the same method described above, the mass fraction of the first polyvinylidene fluoride in electrospinning solution B was controlled to be 20 wt%, and the mass fraction of borate powder was 0.5 wt%, 1.0 wt%, 2.0 wt%, and 2.5 wt%, respectively, to prepare PVDF / B composite nanofiber membranes with different borate doping amounts, denoted as 0.5B, 1.0B, 1.5B, 2.0B, and 2.5B.
[0076] Using the same method described above, the mass fraction of the second polyvinylidene fluoride in electrostatic spray liquid A was controlled to be 8 wt%, and the mass fraction of titanium dioxide was 0.2 wt%, 0.4 wt%, 0.8 wt%, and 1.0 wt%, respectively, to prepare PVDF / BT composite hydrophobic fiber membranes with different titanium dioxide doping amounts, denoted as 0.2T, 0.4T, 0.6T, 0.8T, and 1.0T.
[0077] Using the same method described above, the mass fraction of zirconium dioxide in electrostatic spray liquid B was controlled to be 0.2 wt%, 0.4 wt%, 0.8 wt%, and 1.0 wt%, respectively, to prepare PVDF / BZ composite hydrophobic fiber membranes with different zirconium dioxide doping amounts, denoted as 0.2 Z, 0.4 Z, 0.6 Z, 0.8 Z, and 1.0 Z.
[0078] 2. Characterization and performance evaluation of composite hydrophobic fiber membranes
[0079] (1) Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) analysis
[0080] This embodiment uses a FEIApreo 2S multifunctional high-resolution field emission scanning electron microscope and is equipped with an Oxford Instruments Ultim Max 4.0 energy dispersive spectroscopy analyzer to characterize the nanofiber surface morphology of the fiber membrane and the doping of borazite powder and hydrophobic nanoparticles.
[0081] Figures 1a to 1d SEM images of the PVDF nanofiber membrane, PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane prepared in this embodiment are shown. As can be seen from the images, the PVDF nanofiber membrane without any doping exhibits diverse fiber morphologies and uneven fiber diameters. Figure 1a After doping with borate, the uniformity of fiber morphology was significantly improved, and the fiber diameter became more uniform. Figure 1b Simultaneously, after electrostatic spraying and doping with nano-titanium dioxide / zirconia, nanospheres were clearly observed to adhere to the fiber filaments, supporting the fiber filament structure. Figure 1c and Figure 1dThe nanofiber membranes prepared using the method of this embodiment have uniform fiber thickness, with their diameters mostly concentrated in the range of 160–170 nm.
[0082] Figure 2a , Figure 2b , Figure 3a and Figure 3b The figures show EDS analysis results for the PVDF nanofiber membrane, PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane prepared in this embodiment. The figures demonstrate that the presence of dopants was confirmed by EDS surface scanning, and the dopants are clearly uniformly distributed within the fiber membrane.
[0083] (2) X-ray diffraction (XRD) and X-ray fluorescence spectroscopy (XRF) analysis
[0084] This embodiment uses a German D8 ADVANCE X-ray diffractometer. XRD was used to characterize the PVDF fiber films to determine the crystal structure, β-phase content, and doping status of each fiber film. The scanning 2θ angle range was 10–70°. Elemental analysis of the borosilicate powder was performed using an American ARL Advant X Intellipower™ 3600 X-ray fluorescence spectrometer to determine its elemental content.
[0085] Figure 4 The XRD patterns of the PVDF nanofiber membrane, PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane prepared in this embodiment are shown in the figures. As can be seen from the figures, compared with the XRD results of the undoped PVDF fiber membrane, the characteristic peaks of borate are clearly visible in the XRD results of the PVDF / B, PVDF / BT, and PVDF / BZ fiber membranes after doping, further verifying the successful incorporation of the dopant into the fiber membrane. Furthermore, compared with the pure PVDF fiber membrane, the β-phase characteristic peak of PVDF is significantly increased and the α-phase characteristic peak is somewhat decreased in the other three doped fiber membranes.
[0086] Table 1 shows the XRF elemental spectrum determination results of borazite, which identifies its main elemental composition.
[0087] Table 1
[0088]
[0089] (3) Fourier transform infrared spectroscopy (FT-IR) analysis
[0090] This embodiment uses a Nicolet IS10 Fourier transform infrared spectrometer with a scanning range of 400 cm⁻¹. -1 ~4000cm -1 , is used to characterize the percentage of the β phase in electrospun composite fiber membranes.
[0091] Figure 5 FTIR spectra of the PVDF nanofiber membrane, PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane prepared in this embodiment. The figures show that the ratio of β phase to α phase in the doped fiber membrane is higher than that in the undoped pure PVDF fiber membrane.
[0092] FT-IR absorption follows the Lambert-Beer law, and the relative fraction of the β phase in the fiber membrane can be calculated using formula (3.1.1):
[0093]
[0094] Among them: A β and K β 840cm respectively -1 The absorption peak intensity and absorption coefficient at that point are shown; the absorption coefficient is 6.1 × 10⁻⁶. 4 cm 2 / mol, A α and K α They are 763cm respectively -1 The absorption peak intensity and absorption coefficient at the specified location are shown, with the absorption coefficient being 7.7 × 10⁻⁶. 4 cm 2 / mol.
[0095] Based on Fourier transform infrared spectroscopy analysis, the β phase content in PVDF nanofiber membrane, PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane was calculated to be 73%, 91%, 87%, and 89%, respectively.
[0096] Figure 6a and Figure 6b The figures show the diameter distribution of microspheres in the PVDF / BT composite hydrophobic fiber membrane and the PVDF / BZ composite hydrophobic fiber membrane prepared in this embodiment. As can be seen from the figures, the diameters of the nanospheres are approximately concentrated between 2 and 4 μm.
[0097] (4) Electrical performance testing
[0098] The triboelectric properties of electrospun composite fiber films were tested using a linear motor and an electrometer (a simple triboelectric nanogenerator (TENG) with a contact area of 30*30mm was fabricated by linear reciprocating impact with a force of 5N). The power generation principle of the contact-separation TENG is based on charge transfer caused by contact electrification and electrostatic induction coupling. Under the action of external force, polyamide comes into contact with the PVDF / TM-S surface, triggering the triboelectric effect. Due to the different electron-gaining and losing abilities of the two materials, the polyamide surface becomes positively charged and the PVDF / TM-S surface becomes negatively charged. Currently, the two equal and opposite charges are on the same plane, so there is no potential difference between the two electrodes. When the force applied to the TENG is unloaded, a potential difference is formed between the two electrodes due to the separation of the two charged surfaces. During the gradual separation of the electrode ends, the potential difference drives electrons to move from the PVDF / TM-S end electrode to the polyamide end electrode, generating a transient current until electrostatic equilibrium is reached. When pressure is reapplied to one end of the electrode, reducing the distance between the two ends, a potential difference reappears between the electrodes. This causes electrons to flow from the polyamide electrode back to the PVDF / TM-S electrode, reducing the induced charge on the electrodes. This periodic contact and separation process allows electrons to transfer back and forth in the external circuit, forming a current.
[0099] Figures 7a to 7c , Figures 8a to 8c and Figures 9a to 9c The figures show the triboelectric properties of three composite fiber membranes prepared in this embodiment: PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane. As can be seen from the figures, the PVDF fiber membrane doped only with borate exhibits the highest short-circuit current of 7.1 μA, transferred charge of 102 nC, and open-circuit voltage of 294 V. The membrane doped with sprayed titanium dioxide exhibits the highest short-circuit current of 6.4 μA, transferred charge of 113 nC, and open-circuit voltage of 256 V. The membrane doped with sprayed zirconium dioxide exhibits the highest short-circuit current of 6.1 μA, transferred charge of 117 nC, and open-circuit voltage of 252 V. The fiber membrane doped only with borate shows a significant improvement in electrical properties. While the transferred charge increases after spray-doping with titanium dioxide / zirconium dioxide, the short-circuit current and open-circuit voltage decrease.
[0100] This embodiment uses a DZ5001 dielectric constant tester to measure the dielectric constant and dielectric loss of the electrospun composite fiber membrane using the parallel plate capacitance method. A Ningbo Textile Instrument Factory YG461H fully automatic air permeability meter is used to measure the air permeability by measuring the amount of air flowing through a unit area of the electrospun composite fiber membrane per unit time under a specified pressure difference.
[0101] Figure 10 , Figure 11 and Figure 12 The dielectric constant, air permeability, and dielectric loss of the three composite fiber membranes prepared in this embodiment—PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane—are tested. As can be seen from the figures, the dielectric constant of the spray-doped titanium dioxide / zirconia membrane is improved, and the dielectric loss of the titanium dioxide / zirconia-doped fiber membrane is significantly reduced at high frequencies. Simultaneously, the nanospheres formed by the spray-doped titanium dioxide / zirconia membrane support the fiber filaments, thus greatly improving the air permeability of the PVDF / BT and PVDF / BZ fiber membranes.
[0102] Figure 13 The results of charge transfer tests for three composite fiber membranes prepared in this embodiment—PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane—under different humidity conditions are shown in the figure. As can be seen from the figure, when the ambient humidity exceeds 50%, the charge transfer of the unspray-doped fiber membrane decreases significantly, while the PVDF / BT and PVDF / BZ fiber membranes only show a significant decrease when the ambient humidity reaches 70%.
[0103] (4) Hydrophobicity test
[0104] The water contact angle of the electrospun composite fiber membrane was tested at room temperature. In this embodiment, a German Dataphysics OCA50 contact angle measuring instrument was used. The test results were obtained after the droplet stabilized on the surface of the electrospun composite fiber membrane. The reported data is the average value at five different locations on the surface of the electrospun composite fiber membrane.
[0105] Figures 14a to 14d The images show surface images under a 200x optical microscope of four types of fiber membranes prepared according to embodiments of the present invention: PVDF nanofiber membrane, PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane. As can be seen from the images, compared to the fiber membrane without electrostatic spraying, the PVDF / BT and PVDF / BZ fiber membranes have a smoother surface and no obvious fiber filament shape. This absence of visible fiber filaments and the uniform, dense surface structure can reduce the contact area with water.
[0106] Figure 15a , Figure 15b , Figure 15c and Figure 15dThe figures show the water contact angle test results for four types of fiber membranes prepared in this embodiment: PVDF nanofiber membrane, PVDF / B composite nanofiber membrane, PVDF / BT composite hydrophobic fiber membrane, and PVDF / BZ composite hydrophobic fiber membrane. As can be seen from the figures, the contact angles of the PVDF / BT and PVDF / BZ fiber membranes are 151.7° and 152.2°, respectively, reaching the superhydrophobic standard (150°), which is significantly greater than the other two fiber membranes. This indicates that the electrostatic spraying process for doping with titanium dioxide / zirconia effectively improves the hydrophobic properties of the fiber membrane, thereby enhancing the electroelectric output performance of TENG in high humidity environments.
[0107] Figure 16 This is a schematic diagram of the microstructure of a PVDF / / BT composite hydrophobic fiber membrane (1.5 wt% borosilicate doping and 0.6 wt% titanium dioxide doping). Figure 16 The medium gray spheres represent borosilicate microparticles, while the large white spheres are PVDF microspheres with attached nano-titanium dioxide particles.
[0108] 3. Application testing of PVDF / BT composite hydrophobic fiber membranes and PVDF / BZ composite hydrophobic fiber membranes in triboelectric nanogenerators.
[0109] To verify the mechanical energy harvesting and electrical performance output capabilities of PVDF / BT composite hydrophobic fiber membranes and PVDF / BZ composite hydrophobic fiber membranes, independent TENGs based on PVDF / BT composite hydrophobic fiber membranes (PVDF / BZ composite hydrophobic fiber membranes) were fabricated in practical application tests. The two TENGs achieved a maximum instantaneous power density of 455.6 mW / m³ under different loads through mechanical collision (collision force of 5 N). 2 433.3mW / m 2 ( Figure 17a and Figure 17b The output current remains relatively stable even after 14.4k cycles of collisions. Figure 18a and Figure 18b ).
[0110] To further verify the electrical performance output of PVDF / BT composite hydrophobic fiber membranes and PVDF / BZ composite hydrophobic fiber membranes under real-world conditions, the experimental setup was completely exposed to air for a 7-day test period. For the first 5 days, the temperature and humidity of the test environment were kept undisturbed. However, since the humidity in the natural environment remained around 50%, it was insufficient to verify the performance of these two composite hydrophobic fiber membranes under high humidity conditions. Therefore, starting on the 6th and 7th days, the ambient humidity was artificially increased. The charge transfer of the fiber membranes was sampled at the same time (10:00 AM) during these 7 days. The test results showed no significant change in charge transfer during the first 5 days. On the 6th and 7th days, due to the increased humidity to 80% and 90%, the charge transfer decreased significantly, but a stable output was still maintained. This demonstrates that the PVDF / BT composite hydrophobic fiber membranes and PVDF / BZ composite hydrophobic fiber membranes, due to their unique structure, can still effectively and stably output electrical signals even under high humidity conditions.
[0111] application Figure 20a The circuit diagram in the image shows charging tests performed on capacitors of different capacities. The test results, based on the PVDF / BT composite hydrophobic fiber membrane, indicate that the TENG (Telekinesis Capacitor) meets the requirements for powering small electrical appliances. Capacitors can be used as energy storage devices to provide long-lasting power to electrical appliances, according to... Figure 20b The circuit diagram was successfully connected to power the thermometer, and under periodic impact friction, it successfully lit up 300 small LED bulbs (each LED bulb has a power of 0.04W).
[0112] TENG, based on PVDF / BT composite hydrophobic fiber membrane and PVDF / BZ composite hydrophobic fiber membrane, can also be applied to wearable device sensing because it can adapt to high humidity environments. It can monitor signals when people walk in real time, such as signals when the arm is folded, signals when the leg moves, and signals when the sole of the shoe is subjected to force.
Claims
1. A composite hydrophobic fiber membrane based on a triboelectric nanogenerator, characterized in that, It is composed of polyvinylidene fluoride (PVDF) nanofiber membrane, borosilicate microparticles, hydrophobic nanoparticles, and PVDF microspheres. The borosilicate microparticles are embedded in the filaments of the PVDF nanofiber membrane, and the PVDF microspheres are attached to the filaments of the PVDF nanofiber membrane. Some of the hydrophobic nanoparticles are uniformly attached to the PVDF microspheres, and the other part of the hydrophobic nanoparticles are uniformly attached to the filaments of the PVDF nanofiber membrane. The hydrophobic nanoparticles are titanium dioxide nanoparticles or zirconium dioxide nanoparticles. The composite hydrophobic fiber membrane was prepared by the following method: Step (1): Disperse the borate powder in N,N-dimethylformamide by ultrasonication to obtain a borate dispersion; add the first polyvinylidene fluoride powder to the borate dispersion, heat and stir until the first polyvinylidene fluoride is completely dissolved to obtain an electrospinning solution. Step (2): Disperse the hydrophobic nanoparticles ultrasonically into N,N-dimethylformamide to obtain a hydrophobic nanoparticle dispersion. The hydrophobic nanoparticles are titanium dioxide nanoparticles or zirconium dioxide nanoparticles. Add the second polyvinylidene fluoride powder to the hydrophobic nanoparticle dispersion and heat and stir until the second polyvinylidene fluoride is completely dissolved to obtain an electrostatic spray liquid. Step (3): Place the electrospinning solution and the electrospraying solution in the electrospinning equipment to perform electrospinning and electrospraying simultaneously, and collect the electrospinning jet products; Step (4): The electrostatic jet products collected on the collector are dried. After the drying process, a composite hydrophobic fiber membrane based on a triboelectric nanogenerator is obtained.
2. The composite hydrophobic fiber membrane based on a triboelectric nanogenerator according to claim 1, characterized in that, The thickness of the polyvinylidene fluoride (PVDF) nanofiber membrane is 80–120 μm, and the diameter of the PVDF nanofiber filaments is 160–170 nm; the particle size of the borosilicate microparticles is 100–200 nm, the particle size of the hydrophobic nanoparticles is 80–150 nm, and the diameter of the PVDF microspheres is 0.5–5.0 μm; the mass of the borosilicate microparticles is 0.5–3.0 wt% of the mass of the PVDF fiber membrane, the mass of the hydrophobic nanoparticles is 0.2–1.0 wt% of the mass of the PVDF microspheres, and the mass of the PVDF microspheres is 10–20 wt% of the mass of the PVDF fiber membrane. The mass ratio of hydrophobic nanoparticles attached to polyvinylidene fluoride microspheres to hydrophobic nanoparticles attached to the fibers of polyvinylidene fluoride nanofiber membranes is (10-20):
1.
3. The composite hydrophobic fiber membrane based on a triboelectric nanogenerator according to claim 1, characterized in that, In step (1), the particle size of the borate powder is 100-200 nm. In the electrospinning solution, the mass of the borate powder is 0.5-3.0 wt% of the mass of the first polyvinylidene fluoride. The ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 30-60 kHz for 1.5-3 h at room temperature.
4. The composite hydrophobic fiber membrane based on a triboelectric nanogenerator according to claim 1, characterized in that, In step (1), the average relative molecular mass of the first polyvinylidene fluoride powder is 500,000 to 600,000, the mass fraction of the first polyvinylidene fluoride in the electrospinning solution is 15 to 20 wt%, and the heating and stirring conditions are: stirring at 350 to 500 rpm for 2 to 5 hours at a temperature of 65 to 80°C.
5. The composite hydrophobic fiber membrane based on a triboelectric nanogenerator according to claim 1, characterized in that, In step (2), the size of the hydrophobic nanoparticles is 80-150 nm. In the electrostatic spray liquid, the mass of the hydrophobic nanoparticles is 0.2-1.0 wt% of the mass of the second polyvinylidene fluoride. The ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 40-60 kHz for 60-90 min at room temperature.
6. The composite hydrophobic fiber membrane based on a triboelectric nanogenerator according to claim 1, characterized in that, In step (2), the average relative molecular mass of the second polyvinylidene fluoride in the second polyvinylidene fluoride powder is 400,000 to 450,000, the mass fraction of the second polyvinylidene fluoride in the electrostatic spray liquid is 4 to 10 wt%, and the heating and stirring conditions are: stirring at 350 to 500 rpm for 2 to 3 hours at a temperature of 65 to 80°C.
7. The composite hydrophobic fiber membrane based on a triboelectric nanogenerator according to claim 1, characterized in that, In step (3), the electrospinning equipment is an electrospinning machine capable of electrospinning and electrospraying; when electrospinning and electrospraying are performed simultaneously: the voltage of the high-voltage electrostatic field is 18-20kV, and the propulsion rates of the electrospinning solution and the electrospraying solution are the same, both being 1.0-1.2mL·h. −1 The distance between the tip of the injection nozzle and the aluminum foil collector is 15-18cm, the temperature is controlled within the range of 30-45℃, and the relative humidity is controlled within the range of 40-50%.
8. The composite hydrophobic fiber membrane based on a triboelectric nanogenerator according to claim 1, characterized in that, In step (4), the drying conditions are: 50-60℃, drying for 12-16h; the thickness of the composite hydrophobic fiber membrane obtained by drying is 80-120μm.
9. The composite hydrophobic fiber membrane based on a triboelectric nanogenerator according to claim 1, characterized in that, In step (1), the particle size of the borate powder is 100-200 nm, the mass fraction of the borate powder in the borate dispersion is 0.5-2.5 wt%, and the ultrasonic dispersion conditions are: ultrasonic dispersion at 40 kHz for 2 h at room temperature. The average relative molecular mass of the first polyvinylidene fluoride powder is 600,000, the mass fraction of the first polyvinylidene fluoride in the electrospinning solution is 20 wt%, and the heating and stirring conditions are: stirring at 70°C and 400 rpm for 4 hours. In step (2), the particle size of the hydrophobic nanoparticles is 80-150 nm, the mass fraction of the hydrophobic nanoparticles in the hydrophobic nanoparticle dispersion is 0.2-1.0 wt%, and the ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 40 kHz for 60 min at room temperature. The average relative molecular mass of the second polyvinylidene fluoride powder is 400,000, the mass fraction of the second polyvinylidene fluoride in the electrostatic spray liquid is 8 wt%, and the heating and stirring conditions are: stirring at 70℃ and stirring at 400 rpm for 2 hours. In step (3), the electrospinning equipment is an electrospinning machine capable of electrospinning and electrospraying; when electrospinning and electrospraying are performed simultaneously: the voltage of the high-voltage electrostatic field is 20kV, and the propulsion rates of the electrospinning solution and the electrospraying solution are the same, both being 1.2mL·h. −1 The distance between the tip of the injection nozzle and the aluminum foil collector was 18cm, the temperature was 40℃, and the relative humidity was 40%. In step (4), the drying conditions are: 55℃, drying for 12h; the thickness of the composite hydrophobic fiber membrane obtained by drying is 70~90μm.
Citation Information
Patent Citations
Method for increasing output voltage of electrostatic spinning polymer-matrix friction nano motor
CN107354588A
Friction nanogenerator based on nanofiber membrane and application thereof
CN118456991A
Polymeric composite nanofiber membrane as well as preparation method and application thereof
CN119116517A